2020
DOI: 10.3389/fendo.2020.00284
|View full text |Cite
|
Sign up to set email alerts
|

Dietary α-Linolenic Acid-Rich Flaxseed Oil Exerts Beneficial Effects on Polycystic Ovary Syndrome Through Sex Steroid Hormones—Microbiota—Inflammation Axis in Rats

Abstract: Polycystic ovary syndrome (PCOS) represents a common endocrine-metabolic disorder disease with chronic low-grade inflammation and alteration of intestinal flora. Serving as functional food, flaxseed oil (FO), which is rich in plant-derived α-linolenic acid of omega-3 polyunsaturated fatty acids, has been proven to benefit for chronic metabolic diseases. However, the exact role of dietary FO on PCOS remains largely unclear. In the present study, 6-week-old female Sprague-Dawley rats were randomly divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 103 publications
1
82
0
Order By: Relevance
“…We found that specific bacterial genera were influenced by some components of the diet (i.e., calorie intake and carbohydrates) and were inversely associated with Butyrivibrio abundances. In a rat model, an increased abundance of the Butyrivibrio genus has been associated with diets supplemented with alpha-linoleic acid or prebiotics [44,45], which is consistent with our findings. Our data suggested that some bacterial genera were associated with increased levels of total cholesterol, microbial translocation, and inflammation (Blautia and Catenibacterium), while others were related to a beneficial profile (the reduction in Succinivibrio genus correlated with high immune activation).…”
Section: Discussionsupporting
confidence: 92%
“…We found that specific bacterial genera were influenced by some components of the diet (i.e., calorie intake and carbohydrates) and were inversely associated with Butyrivibrio abundances. In a rat model, an increased abundance of the Butyrivibrio genus has been associated with diets supplemented with alpha-linoleic acid or prebiotics [44,45], which is consistent with our findings. Our data suggested that some bacterial genera were associated with increased levels of total cholesterol, microbial translocation, and inflammation (Blautia and Catenibacterium), while others were related to a beneficial profile (the reduction in Succinivibrio genus correlated with high immune activation).…”
Section: Discussionsupporting
confidence: 92%
“…In the present research, our results also found that some bacteria genera were associated with serum sex hormone levels in PPD patients, such as Faecalibacterium, Lachnospiraceae , and Megamonas , which were significantly different from those in HCs. A recent study has demonstrated that the regulation of sex hormones–microbiota–inflammation axis could ameliorate polycystic ovary syndrome (PCOS), including Faecalibacterium, Parabacteroides, Bifidobacterium , and so on (Wang et al, 2020 ). Another study showed that prenatal androgen exposure causes hypertension and gut microbiota dysbiosis (Sherman et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This diet also increased the amount of omega-3 PUFAs in the mucosa and decreased the ratio of omega-6/omega-3 PUFAs. In addition, the omega-3 PUFA-enriched diet decreased the abundance of pathogenic spirochaetes in the colonic digestive tract and increased the abundance of Actinomycetes , Blautia spp., and Bifidobacteria [ 78 ]. Omega-3 fatty acids inhibit the growth of gut microbiota associated with obesity and peptic ulcer disease and increase the proliferation of beneficial bacteria.…”
Section: Omega-3 Pufas and Inflammationmentioning
confidence: 99%